Energianalys av etanolproduktion - Paulsson, Per (2007)
In this thesis an energy analysis of ethanol production at the ethanol plant of Lantmännen Agroetanol in Norrköping has been performed. The ethanol plant has been studied in combination with Händelöverket, the combined heat and power plant which provides the ethanol process with steam. The purpose of this study was to determine the energy consumption for the whole production chain from grain to ethanol. The analysis has included the energy consumption for cultivation of grain, production of chemicals, the production chain for wood chips, the steam production and the ethanol plant. The grain and wood chips are both considered raw materials there for the energy content in these are not included as energy input in the system. Instead the help energy to produce these two raw materials have been included as input of energy.